A comprehensive study concerning the job satifaction of the instructors associated with students evaluation - Angı, Ayşegül (My University, 2002)
İş tatmini, işle ilgili davranışı öngörmeye yardımcı olması sebebi ile yaygın olarak araştırılmaktadır. Zaman içersindeki gelişimine bakıldığında, önceleri dışsal iş tatminini geliştirmek için çaba sarfedilmişti. İçsel iş tatminin farkedilmesi, bu çabaların insani boyutlara yönlendirmesine yol açmıştır. Hocaların iş tatmini, bilgi aktarımı rollerinden dolayı çok önemlidir. Bu sebeble eğitimin kalitesini muhafaza etmek ve geliştirmek için, iş tatmininde etkili olan iş ile ilgili faktörleri ve bireysel faktörleri anlamak akademik yönetim için son derece önemlidir. İş tatmin seviyelerinin araçlarla tespit edilmesi, işi bırakma, performans değişikliği, fiziksel ve akıl sağlığı üzerindeki olumsuz etkilere karşı önlem alınmasını kolaylaştırmanın yanısıra iletişimi sağlamakta ve iş tutumlarınıda geliştirmektedir. Bu çalışmada Marmara Üniversitesi okutmanlarının iş tatmin seviyelerini saptamak için, demografik soruların yanısıra orjinal araştırma araçları ve Minnesota iş tatmin anketi kullanılmıştır. Araştırmanın kapsamına öğrenci anketlerinin eklenmesi öğrencilerin değerlendirmeleri ile iş tatmin seviyeleri arasında ilişkiyi araştırmayı sağlamıştır. Daha sonra Anova, t-test, Pearson ve Spearman korelasyon analizleri ve regresyon analizlerinden faydalanılmıstır.

Job satisfaction has been substantially examined since it helps predict work behavior. In retrospect, efforts were exerted to improve extrinsic components of job satisfaction. Then, efforts were directed to humanize the work together with the recognition of intrinsic components of job satisfaction. Teachers' job satisfaction is very significant due their role for the transfer of knowledge. Therefore, in order to maintain and promote the quality of education, comprehending job-related and individual factors influencing job satisfaction is very crucial for the academic management. Diagnosing job satisfaction level with the instruments not only facilitates to take precautions against such adverse consequences as withdrawal from the job, changes in performance, and effects on physical and mental health, but also provides communication flow and promotion of work related attitudes. In this study, so as to find out the job satisfaction levels of instructors at Marmara University; apart from demographic questions, original research instruments together with the Minnesota Satisfaction Questionnaire and are implemented. Adding students' questionnaire to the research provides a broader understanding of the relation between students' evaluation and job satisfaction. Then analyses of reliability, one-way ANOVA, the independent-samples t-test, the paired t-test, Pearson and Spearman correlation and regression are performed.
Keywords: İş Tatmini